(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
Summary: 1. Introduction - 2. Constitutional project of ecclesiastical politics and cultural resistance to a correct interpretation of the fundamental provisions of freedom - 3. Secularity of the legal system, religious pluralism and human freedoms. ABSTRACT: The problems that derive from the growing multicultural and multi-religious characterization of our society raise a number of questions regarding the difficulties encountered in identifying rules of coexistence that could be genuinely respectful of the ideal and spiritual dimension of the human person. In particular, it is in question the ability of the system of bilateral agreements between the State and the religious organizations to really enhance the individual religiosity, which is constitutionally protected in its instrumentality for the promotion and growth of the human being. Several doubts also concern the discretionary and political selection, exercised by public authorities, of religious organizations deserving an access to bilateral regulation of relationships. In a more and more plural and heterogeneous social reality, the exclusion from the special legislation of the newly established spiritual groups in the country does not seem to be respectful of a neutral and correct interpretation of the constitutional dictate.